2018
DOI: 10.1016/j.cclet.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide coordination with 14 lanthanides studied by isothermal titration calorimetry

Abstract: ITC reveals the increasingly importance of entropy for heavier lanthanides binding to nucleotides. The phosphate group forming chelating effect with purine bases but not with pyrimidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…All samples spontaneously formed particles as judged from increased turbidity (Figure 1B), and the Tb 3+ /GMP sample also showed strong green luminescence, also indicating the coordination reaction. 28 Previous work showed that both the nucleobase and the phosphate of these nucleotides are required for forming such CPs, 28,40,41 and a proposed structure of Ln 3+ /GMP is also shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…All samples spontaneously formed particles as judged from increased turbidity (Figure 1B), and the Tb 3+ /GMP sample also showed strong green luminescence, also indicating the coordination reaction. 28 Previous work showed that both the nucleobase and the phosphate of these nucleotides are required for forming such CPs, 28,40,41 and a proposed structure of Ln 3+ /GMP is also shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 90%
“…28,39 We have recently performed a systematic titration of lanthanides to nucleotides and found a continuous thermodynamic trend. 40 We hypothesize that it might be possible to continuously tune the interaction strength between DNA and lanthanide containing CPs by varying the lanthanide and/or nucleotides. In this work, we wanted to achieve two goals: (1) a careful study of DNA adsorption by such CPs in terms of material composition and interaction forces; and (2) tuning DNA adsorption affinity.…”
Section: Introductionmentioning
confidence: 99%
“…We did as ystematic isothermal titration calorimetry (ITC) study to follow the heatp rofile from adding trivalentl anthanide ions to GMP ( Figure 6) and other nucleotides. [34] All the ions have as imilarb inding affinity,b ut the heat profile gradually changed from releasing heat to absorbing heat, suggesting the contribution of entropyi ncreased with increasing atomic number of lanthanide. Another interesting observation was the difference between pyrimidine and purinem onophosphates with respect to lanthanide binding.…”
Section: Lanthanidesmentioning
confidence: 99%
“…Actually,b inding to phosphate is even more important since none of the nucleobases alone can form CPs with lanthanides. [34] An early study by Nishiyabua nd co-workers explored the binding betweenl anthanidesa nd nucleotide monophosphates. [27] The general reaction scheme is shown in Figure 5A.T hey observed CP nanoparticles between 30-200 nm in diameter from SEM ( Figure 5B)a nd TEM ( Figure 5C).…”
Section: Lanthanidesmentioning
confidence: 99%
See 1 more Smart Citation